2010
DOI: 10.1016/j.neuron.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Time-Dependent Plasticity and Heterosynaptic Competition Organize Networks to Produce Long Scale-Free Sequences of Neural Activity

Abstract: Sequential neural activity patterns are as ubiquitous as the outputs they drive, which include motor gestures and sequential cognitive processes. Neural sequences are long, compared to the activation durations of participating neurons, and sequence coding is sparse. Numerous studies demonstrate that spike-time-dependent plasticity (STDP), the primary known mechanism for temporal order learning in neurons, cannot organize networks to generate long sequences, raising the question of how such networks are formed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
343
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(354 citation statements)
references
References 60 publications
11
343
0
Order By: Relevance
“…Typical computational models of sequence learning employ networks of neurons (Jun and Jin, 2007;Fiete et al, 2010;Brea et al, 2013) or populations (Abbott and Blum, 1996) that are each active for equal amounts of time during replay. However, sensory and motor processes can be governed by networks whose neurons have a fixed stimulus tuning (Xu et al, 2012;Gavornik and Bear, 2014).…”
Section: Learning Both the Precise Timing And Order Of Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Typical computational models of sequence learning employ networks of neurons (Jun and Jin, 2007;Fiete et al, 2010;Brea et al, 2013) or populations (Abbott and Blum, 1996) that are each active for equal amounts of time during replay. However, sensory and motor processes can be governed by networks whose neurons have a fixed stimulus tuning (Xu et al, 2012;Gavornik and Bear, 2014).…”
Section: Learning Both the Precise Timing And Order Of Sequencesmentioning
confidence: 99%
“…A complementary approach has been used to infer time by fitting a maximum likelihood model to the rates and phases of spiking neurons in hippocampal networks (Itskov et al, 2011). Our approach is most similar to previous studies that utilize discrete populations or neurons to represent serial order (Grossberg and Merrill, 1992;Abbott and Blum, 1996;Fiete et al, 2010;Brea et al, 2013). Namely, we assume that the memory of each individual event duration is learned in parallel with the others as in Fiete et al (2010), in contrast to the serial building of chains demonstrated in the model of Jun and Jin (2007).…”
Section: Comparison To Previous Models Of Interval Timingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent computational modelling suggests that the interaction of these processes is critical to establish and maintain appropriate conditions for transient dynamics during cognitive processing, and the examination of a unified model of neural and synaptic plasticity is therefore a critical direction for future theoretical studies [86][87][88][89]. More generally, an examination of the synaptic and neural dynamics generated by the triphasic STDP rule in network models of hippocampal function with more realistic activity patterns, including theta modulation and phase precession, would contribute significantly to the understanding of hippocampal function during putative learning behaviour [90].…”
Section: Discussionmentioning
confidence: 99%